Transforming triglycerides and fatty acids into biofuels - Lestari, S.; Mäki-Arvela, P.; Beltramini, J.; Lu, G.M.; Murzin, D.Y.
Fuels derived from biobased materials are attracting attention for their potential in securing the energy supply and protecting the environment. In this Minireview, we evaluate the use of biobased sources, particularly fatty acids and triglycerides from seed oils and animal fats, as fuels. The physical and chemical properties of these fatty acids and triglycerides are discussed, including the link to their sources and current availability to meet fuel demands. The current technologies, also known as the first-generation ones, for converting triglycerides into fuels are covered, including conventional methods such as transesterification, pyrolysis, cracking, and emulsions. Recent, secondgeneration technological developments that lead to more commercially viable biofuels based on diesel-like hydrocarbons are also discussed.
Keywords: ANIMAL FAT; BIO-BASED MATERIALS; BIOBASED; CONVENTIONAL METHODS; CURRENT TECHNOLOGY; ENERGY SUPPLIES; FUEL DEMAND; PHYSICAL AND CHEMICAL PROPERTIES; SEED OIL; TECHNOLOGICAL DEVELOPMENT